Sexual function after fractional microablative CO2 laser in women with vulvovaginal atrophy. (April 2015) - Salvatore, S.; Nappi, R. E.; Parma, M.; Chionna, R.; Lagona, F.; Zerbinati, N.; Ferrero, S.; Origoni, M.; Candiani, M.; Leone Roberti Maggiore, U.
Abstract: Objective To investigate the effects of fractional microablative CO2 laser on sexual function and overall satisfaction with sexual life in postmenopausal women with vulvovaginal atrophy (VVA). Method This prospective study included 77 postmenopausal women (mean age 60.6 ± 6.2 years) treated for VVA symptoms with the fractional microablative CO2 laser system (SmartXide 2 V 2 LR, Monalisa Touch, DEKA, Florence, Italy). Sexual function and quality of life were evaluated with the Female Sexual Function Index (FSFI) and the Short Form 12 (SF-12), respectively, both at baseline and at 12-week follow-up. A 10-mm visual analog scale was used to measure the overall satisfaction with sexual life and the intensity of VVA symptoms (vaginal burning, vaginal itching, vaginal dryness, dyspareunia and dysuria) before and after the study period. Results We observed a significant improvement in the total score and the scores in each specific domain of the FSFI at 12-week follow-up compared to baseline ( p < 0.001). After concluding the laser treatment, the overall satisfaction with sexual life significantly improved ( p < 0.001). Seventeen (85%) out of 20 (26%) women, not sexually active because of VVA severity at baseline, regained a normal sexual life at the 12-week follow-up. Finally, we also found a significant improvement in each VVA symptom ( p < 0.001) and in quality-of-life evaluation, both for the scores in the physical ( p = 0.013) and mental ( p = 0.002) domains. Conclusions Fractional microablative CO2 laser treatment is associated with a significant improvement of sexual function and satisfaction with sexual life in postmenopausal women with VVA symptoms.